Implementing a quality improvement initiative for private healthcare facilities to achieve accreditation: experience from India - Tapas Sadasivan Nair; Parvez Memon; Sanjay Tripathi; Ashish Srivastava; Meshach Sunny Kujur; Deepti Singh; Parag Bhamare; Vikas Yadav; Vineet Kumar Srivastava; Suranjeen Prasad Pallipamula; Gulnoza Usmanova; Somesh Kumar (BMC, 2023)
Abstract Background The Manyata program is a quality improvement initiative for private healthcare facilities in India which provided maternity care services. Under this initiative, technical assistance was provided to selected facilities in the states of Uttar Pradesh, Jharkhand and Maharashtra which were interested in obtaining 'entry level certification' under the National Accreditation Board for Hospitals and Healthcare Providers (NABH) for provision of quality services. This paper describes the change in quality at those Manyata-supported facilities when assessed by the NABH standards of care. Methods Twenty-eight private-sector facilities underwent NABH assessments in the three states from August 2017 to February 2019. Baseline assessment (by program staff) and NABH assessment (by NABH assessors) findings were compared to assess the change in quality of care as per NABH standards of care. The reported performance gaps from NABH assessments were then also classified by thematic areas and suggested corrective actions based on program implementation experience. Results The overall adherence to NABH standards of care improved from 9% in the baseline assessment to 80% in the NABH assessment. A total of 831 performance gaps were identified by the NABH assessments, of which documentation issues accounted for a majority (70%), followed by training (19%). Most performance gaps could be corrected either by revising existing documentation or creating new documentation (62%), or by orienting facility staff on various protocols (35%). Conclusion While the adherence of facilities to the NABH standards of care improved considerably, certain performance gaps remained, which were primarily related to documentation of facility policies and protocols and training of staff, and required corrective actions for the facilities to achieve NABH entry level certification.